(untitled) (Texas Journal of Engineering and Technology, 2023)
New mixed polyfunctional catalysts for the hydration of acetylene to acetaldehyde and acetone have been developed, their properties have been developed, and various ways of formation of acetylene by the reaction of hydration condensation have been proposed